Acute and chronic effects of diazepam on the polychaete Hediste diversicolor: Antioxidant, metabolic, pharmacologic, neurotoxic and behavioural mechanistic traits - Nogueira, Ana Filipa (2022)
Pharmaceutical drugs are widespread environmental contaminants, but data about their adverse effects are still limited to a few compounds. This study analyzed the acute (96 h) and chronic (28 days) impacts of environmentally realistic levels of diazepam (acute exposure: 0.001, 0.01, 0.1, 1, 10 μg/L; chronic exposure: 0.1, 1, 10, 100, 1000 ng/L), in the polychaete Hediste diversicolor, by measuring behavioral and biochemical (catalase [CAT], glutathione-S-transferases [GSTs], cholinesterases [ChEs], glutathione peroxidase [GPx], lipid peroxidation [TBARS]) parameters. Acute exposure to diazepam altered behavioral traits, decreasing burrowing times and causing hyperactivity, whilst burrowing time increased and hypoactivity resulted after chronic exposure. All biomarkers were affected after the chronic exposure, with the exception of lipid peroxidation. Our data demonstrate that realistic levels of diazepam may impair behavioral and biochemical traits in polychaetes, suggesting that diazepam exposure presents a significant challenge to the environment that supports these organisms.